2021
DOI: 10.3390/nano11102558
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable Pickering Emulsions with Xylan Hydrate Nanocrystals

Abstract: Xylan is a highly abundant plant-based biopolymer. Original xylans in plants are in an amorphous state, but deacetylated and low-branched xylan can form a crystalline structure with water molecules. The utilizations of xylan have been limited to bulk applications either with inconsistency and uncertainty or with extensive chemical derivatization due to the insufficient studies on its crystallization. The applications of xylan could be greatly broadened in advanced green materials if xylan crystals are effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…138,139 It is possible to prepare nanocrystals with xylan extracted from birchwood kraft pulp 140 as well as nanoparticles from xylan and xylan derivates. 141−143 Xylan nanocrystals from sugar cane bagasse have been successfully utilized as Pickering emulsifiers, 144 which might indicate that wood-derived xylan nanocrystals have the potential to be used similarly. Additionally, insoluble clusters of alkaliextracted xylans from birch and beech also demonstrated efficient stabilization properties.…”
Section: Degree Of Polymerization (Dp)mentioning
confidence: 99%
See 1 more Smart Citation
“…138,139 It is possible to prepare nanocrystals with xylan extracted from birchwood kraft pulp 140 as well as nanoparticles from xylan and xylan derivates. 141−143 Xylan nanocrystals from sugar cane bagasse have been successfully utilized as Pickering emulsifiers, 144 which might indicate that wood-derived xylan nanocrystals have the potential to be used similarly. Additionally, insoluble clusters of alkaliextracted xylans from birch and beech also demonstrated efficient stabilization properties.…”
Section: Degree Of Polymerization (Dp)mentioning
confidence: 99%
“…The particles are considered to be adsorbed irreversibly at the oil–water interface due to the high free energy barrier associated with their desorption . There have been many explorations into the use of polysaccharide-based solid particles as Pickering emulsifiers. , It is possible to prepare nanocrystals with xylan extracted from birchwood kraft pulp as well as nanoparticles from xylan and xylan derivates. Xylan nanocrystals from sugar cane bagasse have been successfully utilized as Pickering emulsifiers, which might indicate that wood-derived xylan nanocrystals have the potential to be used similarly. Additionally, insoluble clusters of alkali-extracted xylans from birch and beech also demonstrated efficient stabilization properties .…”
Section: Key Physicochemical Properties Of Wood Hemicelluloses and Th...mentioning
confidence: 99%
“…51 The homogenization process was easy and rapid. 52 However, during the preparation process of Pickering emulsions, there are the risks of particle deformation or disruption similar to rotor-stator homogenization and high-pressure homogenization. Also, the obtained Pickering emulsion exhibited a broad size distribution.…”
Section: Ultrasonic Emulsificationmentioning
confidence: 99%
“…Enzymatic removal of xylan side chains has been shown to influence the crystallinity of xylan aggregates, suggesting a negative correlation between the degree of substitution and crystallinity. , In addition, recent work using glycosynthases, glycoside hydrolases modified to function as transferases, demonstrated that long xylan chains can be generated by stitching together chemically synthesized xylan oligosaccharide fluorides of defined structures by repetitive condensation. , Glycosynthase-formed xylans can assemble into crystalline aggregates where the degree of crystallinity was found to be dependent not just on side-chain abundance but also on the linkage and structural features of side-chain groups decorating the polymers . Further, studies have investigated the formation of xylan hydrate nanocrystals from the mild ultrasonic treatment of aqueous xylan suspensions . However, the mechanisms that might govern the processes of xylan aggregation have remained largely unexplored.…”
mentioning
confidence: 99%
“…14 Further, studies have investigated the formation of xylan hydrate nanocrystals from the mild ultrasonic treatment of aqueous xylan suspensions. 22 However, the mechanisms that might govern the processes of xylan aggregation have remained largely unexplored.…”
mentioning
confidence: 99%